2004
DOI: 10.1038/sj.npp.1300525
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Reductions in the Level of Glial Fibrillary Acidic Protein in the Prefrontal Cortex in Major Depression

Abstract: The density of glial cells is reduced in certain layers of the dorsolateral prefrontal cortex in major depressive disorder (MDD). Moreover, there are reductions in the packing density of glial fibrillary acidic protein (GFAP) immunoreactive astrocytes in the same cortical layers in younger subjects with MDD. The objective of the present study was to test if the level of GFAP is preferentially decreased in younger subjects with MDD, and whether GFAP levels are correlated with the age of onset of depression. Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
125
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(145 citation statements)
references
References 25 publications
11
125
2
2
Order By: Relevance
“…In addition, we found reduced density of GFAP-immunostained astrocytes in the LC region in the MDD samples compared with matched control samples. Reduced GFAP immunoreactivity in MDD has been reported for anterior cingulate cortex white matter, 42 dorsolateral prefrontal cortex deep layers, 43,44 the amygdala 16 and the cerebellum. 45 Interestingly, Wistar-Kyoto rats (a strain often used as a model of depression and stress sensitivity) exhibit lower levels of GFAP immunoreactivity in the cerebral cortex and amygdala and a reduced number of GFAPimmunoreactive astrocytes compared with Sprague-Dawley rats.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, we found reduced density of GFAP-immunostained astrocytes in the LC region in the MDD samples compared with matched control samples. Reduced GFAP immunoreactivity in MDD has been reported for anterior cingulate cortex white matter, 42 dorsolateral prefrontal cortex deep layers, 43,44 the amygdala 16 and the cerebellum. 45 Interestingly, Wistar-Kyoto rats (a strain often used as a model of depression and stress sensitivity) exhibit lower levels of GFAP immunoreactivity in the cerebral cortex and amygdala and a reduced number of GFAPimmunoreactive astrocytes compared with Sprague-Dawley rats.…”
Section: Discussionmentioning
confidence: 91%
“…[170][171][172][173][174] Although some reports did not differentiate between the loss of microglial cells or astrocytes, this difference is crucial due to the different effects of the type 1/type 2 immune response. Recent studies show that in particular astrocytes are diminished in MD, [175][176][177] although the data are not fully consistent. 178 A loss of astrocytes was particularly observed in younger depressed patients: the lack of glial fibrillary acidic acid (GFAP)-immunoreactive astrocytes reflects a lowered activity of responsiveness in those cells.…”
Section: Astrocytes Microglia and Type 1/type 2 Responsementioning
confidence: 88%
“…Previous work has shown that exposure to 21 days of restraint stress in rats decreased the length and number of branch points of dendrites in the anterior Cg and prelimbic cortices (Radley et al, 2004). Neuroimaging and postmortem studies have clearly demonstrated reductions in frontal lobe volumes and decreases in cell number and/ size in anterior Cg, dorsolateral, prefrontal, subgenual, and orbitofrontal cortices (Rajkowska, 2000;Si et al, 2004). The higher cognitive areas of the anterior Cg, Fr cortices, and CeA where we observed regulation of Bcl-2 correspond well with regions where volumetric and structural impairments are observed in patients with depression.…”
Section: Discussionmentioning
confidence: 98%